Some comments on Passer italiae-like of south Italy, Sicily and Malta - Bruno Massa (PAGEPress Publications, 2021)
The authors summarize the results obtained over a period of about 150 years by various authors on the taxonomic position of Sparrows present in southern Italy, Sicily and Malta, identified on several occasions as Passer italiae, P. hispaniolensis or as hybrids of the two species. Based on the latest research and the analysis of the genome of the sparrows of Corsica, Crete, southern Italy, Sicily and Malta, it appears that it has finally been possible to establish that these populations possess a different degree of hybridization between P. italiae and P. hispaniolensis, with less genes of P. hispaniolensis in northern regions and more in southern ones. Therefore, the authors propose to name these populations Passer italiae x hispaniolensis.